TRANSITION FROM INSTITUTIONAL PARADIGMS TO SUSTAINABILITY: A BIBLIOMETRIC REVIEW OF SCIENTIFIC PRODUCTION - da Silva, Antonio Willamys Fernandes; Scharffhausen, Jean-Baptiste Marc; Santos, Ilanna Clara Macedo; Marques, Yasmin da Conceição; Kraho, Karlessandra Potwyn Souza Lima; Lima, Raquel da Costa; Moura, Isadora Rodrigues; Carvalho, Kamilly Raquel Sousa Meireles; dos Anjos, Sttéphany Romana da Silva (Seven Editora, 2026)
This research aims to conduct a bibliometric mapping of institutional change related to sustainability. To this end, a search was carried out in the Scopus, SciELO, and Web of Science databases using the keywords "institutional change and energy and environmental science." The search was limited to scientific journals from the last five years. The objective was to perform a bibliometric mapping on the topic of institutional change and sustainability, and to analyze the performance of the bibliometric results, considering several aspects. The method used in the research was descriptive, which aims to transcribe, describe, interpret, and explain the results obtained with the aid of bibliometric analysis. This aims to identify and analyze the profile of scientific production on a given topic, using a quantitative approach through descriptive statistics. From the point of view of bibliometric networks, it was observed, through the mapping of keywords, that the researched topic is inserted in different contexts, separated into three aspects: 1 – institutional change, 2 – institutional structure, and 3 – sustainability. All the selected articles point to institutional change as one of the mitigating actions in relation to sustainable development. This change involves the restructuring of institutions. The process is slow and gradual because there are resistance mechanisms, mainly from the economic sector, but also partly from the academic sector. Researchers argue that the Sustainable Development Goals (SDGs) have a limited and inadequate conceptualization, which hinders their practical application. Although they aim to promote sustainable patterns, the SDGs fail to provide clear targets and effective guidance for the necessary institutional changes. The authors report that a holistic view of the challenges is important and describe the blockchain-based micro-network model, proposing changes in institutions as well as in the scientific and academic environment.